2011
DOI: 10.1002/jpln.201000318
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient and carbon balances in organic vegetable production on an irrigated, sandy soil in northern Oman

Abstract: Our understanding of nutrient and carbon (C) fluxes in irrigated organic cropping systems of subtropical regions is limited. Therefore, leaching of mineral nitrogen (N) and phosphorus (P), gaseous emissions of NH 3 , N 2 O, CO 2 , and CH 4 , and total matter balances were measured over 24 months comprising a total cropping period of 260 d in an organic-cropping-systems experiment near Sohar (Oman). The experiment on an irrigated sandy soil with four replications comprised two manure types (ORG1 and ORG2) chara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
28
3

Year Published

2015
2015
2018
2018

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 25 publications
(35 citation statements)
references
References 19 publications
4
28
3
Order By: Relevance
“…This it is likely due to the very high temperatures in the Omani lowlands. Regardless of the cropping system, cumulative annual leaching losses of mineral N and P were very low compared to the findings from sandy lowland soils by Siegfried et al (2011). These low rates may be due to a combination of low seepage, differences in the particle size distribution and the higher organic C content of our soils.…”
Section: Discussioncontrasting
confidence: 56%
See 3 more Smart Citations
“…This it is likely due to the very high temperatures in the Omani lowlands. Regardless of the cropping system, cumulative annual leaching losses of mineral N and P were very low compared to the findings from sandy lowland soils by Siegfried et al (2011). These low rates may be due to a combination of low seepage, differences in the particle size distribution and the higher organic C content of our soils.…”
Section: Discussioncontrasting
confidence: 56%
“…2). In their study of gaseous N and C losses from the northern Oman costal plain of Al-Batinah, Siegfried et al (2011) reported similarly high fluxes that were related to a very fast C and nutrient turnover. Although they used lower manure application rates than in our study, total gaseous N and C losses were similar.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…For example, in an organic vegetable cropping system, compost N mineralization was not synchronous with N assimilation, resulting in a leaching risk under inappropriate practices such as the absence of a winter cover crop (Evanylo et al 2008). Furthermore, for irrigated organic vegetables grown under arid subtropical climate conditions, a very fast turnover of the amendments resulted in high C and N volatilization (Siegfried et al 2011). Consequently, sources, rate, timing, and method of amendment application will influence soil temperature, soil moisture, and nutrient availability (Gaskell and Smith 2007).…”
Section: B Nutrient Budgetingmentioning
confidence: 99%